The Feller diffusion, filter rules and abnormal stock returns. Issue 5 (24th March 2018) - Docherty, Paul; Dong, Yizhe; Song, Xiaojing; Tippett, Mark
Abstract: We determine the conditional expected logarithmic (i.e. continuously compounded) return on a stock whose price evolves in terms of the Feller diffusion and then use it to demonstrate how one must know the exact probability density that describes a stock's return before one can determine the correct way to calculate the abnormal returns that accrue on the stock. We show in particular that misspecification of the stochastic process which generates a stock's price will lead to systematic biases in the abnormal returns calculated on the stock. We examine the implications this has for the proper conduct of empirical work and for the evaluation of stock and portfolio performance.